Ecogenic Beachcomber - Md Hamzah, Muhammad Akmal; Azham, Muhammad Izz Zafri; Mohd Khairi, Muhammad Akashah; Ahmad Yusof, Nur Syuhada; Adanan, Syaza Aqilah (2018)
BC Corp is an organization that is formed under a partnership that produces an innovative rubbish collector machine which is beachcomber. Our business main goal is to be one of the top company in Malaysia by providing our main product which is Ecogenic Beachcomber that is unique and eco-safe. Our company also focuses on providing good quality machine to customer and give satisfaction to customer when using our product. BC Corp creates Ecogenic Beachcomber with some of safety element to ensure that the user and people near the machine are in protected from any unwanted incident. The concept of our organization is to provide the best products that can help cleamthe environment of the beach around the country.